2019
DOI: 10.3389/fneur.2019.00365
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Head Impulse Test to Assess Oscillopsia in Bilateral Vestibulopathy

Abstract: Introduction: Bilateral vestibulopathy (BV) is a chronic condition in which vestibular function is severely impaired or absent on both ears. Oscillopsia is one of the main symptoms of BV. Oscillopsia can be quantified objectively by functional vestibular tests, and subjectively by questionnaires. Recently, a new technique for testing functionally effective gaze stabilization was developed: the functional Head Impulse Test (fHIT). This study compared the fHIT with the Dynamic Visual Acuity assessed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…In this study and the majority of other studies ( 21 , 49 ) reporting DVA testing during treadmill walking, no patients dropped out during walking at 2 km/h. Only the study of van Dooren et al ( 50 ) reported a dropout of 9% at 2 km/h. For DVA testing at 4 km/h, the dropout rates ranged between 5% ( 21 ) and 14% ( 49 ), while in the present study this was 11%.…”
Section: Discussionmentioning
confidence: 98%
“…In this study and the majority of other studies ( 21 , 49 ) reporting DVA testing during treadmill walking, no patients dropped out during walking at 2 km/h. Only the study of van Dooren et al ( 50 ) reported a dropout of 9% at 2 km/h. For DVA testing at 4 km/h, the dropout rates ranged between 5% ( 21 ) and 14% ( 49 ), while in the present study this was 11%.…”
Section: Discussionmentioning
confidence: 98%
“…This test, commercialized by BeOnSolutions society ( ), is based on the ability of a subject to read an optotype briefly presented during impulsive head rotations at varying angular accelerations [ 26 ]. Several studies have been conducted already using this test in adults from the general population [ 15 , 27 ] or with vestibular neuritis [ 16 , 28 ]. Briefly, the testing procedure was as follows: the child was seated on a chair placed at 150 cm distance from a computer screen connected to the fHIT device ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The test has shown effectiveness when evaluating acute unilateral vestibulopathy [ 57 ] and the effect of a prototype vestibular implant [ 58 ]. Although fHIT moderately correlates with oscillopsia severity, no correlation was observed between fHIT and the DVA test on a treadmill [ 59 ]. These tests seem complementary and do not substitute for each other.…”
Section: Testing Of Dynamic Visual Acuitymentioning
confidence: 99%
“…DVA is a functional outcome of all systems involved: VOR, the oculomotor system, and central processing of signals [ 59 ]. For instance, internal feed-forward commands can mediate gaze [ 60 ], gait stabilization strategies can help to reduce head oscillations [ 61 ], and covert saccades improve DVA in patients with unilateral vestibulopathy [ 34 , 62 ].…”
Section: Testing Of Dynamic Visual Acuitymentioning
confidence: 99%